A case report of cerebral venous sinus thrombosis presenting with rapidly progressive dementia - Li, Yaqiang; Zhang, Mei; Xue, Min; Wei, Ming; He, Jiale; Dong, Chunhui (Frontiers in Medicine, 2022)
Background: Cerebral venous sinus thrombosis (CVST) is a rare but serious and treatable cause of neurologic symptoms. As a consequence of the variable clinical manifestations, CVST was often misdiagnosed. According to published case reports, the common clinical manifestations of CVST include headache, focal neurological deficit, epilepsy, papilledema, etc. It is rare, nevertheless, to mention cases of rapidly progressive dementia (RPD). Case Presentation: We describe a case of a 62-year-old retired male accountant presenting with slow reaction and memory decline initially. Until two months later, his memory loss and unresponsiveness worsened significantly, and he could not even complete simple tasks like brushing his teeth, washing his face, washing his feet, and dressing himself, and sometimes developed fecal incontinence. Conclusion: This case demonstrates the clinical heterogeneity of CVST. CVST should be taken into account for differential diagnosis of rapidly progressive dementia. This case study provides new information for the diagnosis of CVST and the classification of the clinical characteristics.